If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7b-2b=3b+b+6
We move all terms to the left:
7b-2b-(3b+b+6)=0
We add all the numbers together, and all the variables
7b-2b-(4b+6)=0
We add all the numbers together, and all the variables
5b-(4b+6)=0
We get rid of parentheses
5b-4b-6=0
We add all the numbers together, and all the variables
b-6=0
We move all terms containing b to the left, all other terms to the right
b=6
| 8x-23+3×+22=0 | | -10+-7k=-66 | | 5x-30=7x+8 | | y−-10/4=4 | | -29u=-3 | | -4=3x-1=2x+1+2x | | 94=31+3w | | -5(k-5)=-25-5k | | 3n-2+2(2n+1)=5n+7+7 | | 170=7x | | 10x+8=310 | | -15w-21=-111 | | 15=-2(2t+-1 | | 4x+10(x-4)+(x-1)=24 | | 3+7(3x+3)=22 | | x×x=24 | | 10-5(3x+2)=-15x | | -(x=3)=2x-6 | | n+5/12-2n-3/8=2 | | 67=27+2y | | 3.2(s+10)=32 | | h+11/12=1201/2 | | x•x=24 | | -8(y-1.25)=4 | | 0.33x+15=2.67x-22 | | 2(x=3)-4= | | j/3-5=4 | | 6z+7z=65 | | a-(-19)=5 | | 12/28=9/g | | 10b+-45=-43 | | 2(69+3)=18-3(16-3d) |